Qualitative Research-Does It Have a Place in - Anthony S. Blinkhorn, BDS, MSc, PhD, FDSRCS (Blackwell Synergy, 2000)
Finding out "what the people really want" have become the watchwords of many working in politics and commercial organizations. But how to pinpoint these elusive views can be a difficult and time-consuming exercise. One way, which has become the mantra for many, is qualitative research- particularly, gathering specific subsections of the population into small focus groups and seelung a consensus view